Analysis of an innovative business model: the freemium and its applications - Picquendaele, Laetitia de Crombrugghe de (2016)
This master thesis will investigate the freemium business model, raising on the questions: “Why is the freemium business model innovative and what are its success factors?” The aim is to analyse this business model by confronting theory and practice. Therefore, the document begins with a description discussion of the freemium business model. The literature review concludes by determining the success factors of the business model innovation and of the freemium model. The theory in this first part is then compared to practical examples in the second part. Five different cases of the freemium model are discussed with the help of the tools defined previously. The comparison will be made between the theory and the practice, the common points will be highlighted and the differences will be discussed. The information comes from different interviews with the founder or an employee of the company. Important results are the following: 1) for a successful freemium business model the dividing line between the free and premium product must be clearly established, 2) the freemium business model is disruptive because it forces the competition to also have a free offer, 3) the freemium can be a useful tool to enter the market when the value proposition of the offered product or service is not well understood by the market. These observations are in line with the initial aim of the study, which is to identify what makes the freemium model work. The thesis aim at being helpful in the successful implementation of the freemium model.